THE SOCIÉTÉ ANONYME: FROM JOINT ACCOUNT TO BUSINESS CORPORATION. - Howard, Stanley E. (The Accounting Review, 1933)
The French Code de Commerce, a law promulgated in 1807, contains a striking instance of an official changing of usage in a matter of business terminology. In making legislative recognition of the business corporation, the framers of the code applied to the corporation, as its official designation, the term "société anonyme," which means anonymous society. In so doing they appropriated a term which hitherto had been employed both by laymen and by members of the legal profession to designate various types of informal associations of business men, not one of which at all resembled a corporation. These forms of association were, in fact, characterized by features which are diametrically the opposite of those which characterize the business corporation. Yet the change in the official meaning of the term, société anonyme was effected, and the new meaning has apparently entered into common usage on a permanent basis. One of the earliest forms of the société anonyme appeared as the association of persons who participated secretly in the farming of taxes. The tax farmer for a town, city or other district associated with himself several capitalists to participate in the profits or losses of the undertaking.